Peran OHCHR Meningkatkan Promosi Penegakan Hak Anak Melalui Universal Periodic Review di Bolivia pada tahun 2010-2014 - Samosir, Agustina; Sushanti, Sukma; Widya Nugraha, A.A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT Office of the United Nations High Commisioner for Human Rights (OHCHR) which focuses on the issue of human rights created the Universal Periodic System mechanism. This research will look at how OHCHR through the UPR mechanism helps improve the enforcement of children's rights in Bolivia. The research period was from the first cycle Bolivia joined the UPR mechanism in 2010 to 2014The research also used descriptive qualitative research with the role of international organizations concept. This concept analyzes the role of OHCHR as an independent actor and the efforts made by OHCHR explain the function of OHCHR for the role it applies. After the research was carried out, it was found that OHCHR was able to encourage Bolivia to join the UPR mechanism and carry out several recommendations on the situation of children's rights because OHCHR showed the independence and influence of the power of OHCHR. Keywords: The Rights of Child, OHCHR, Universal Periodic Review, Role and Function of International Organization.